Sitting on a Volcano: Domestic Violence in Indonesia Following Two Volcano Eruptions - Maximilian Schwefer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
This is the first study to provide pre- and post-treatment family-level data on the impact of volcano eruptions on domestic violence. I use data from 2,024 families in Indonesia, of which a subset has been exposed to two eruptions. Findings confirm an increase in domestic violence of four percent in the treatment group. The proposed channel is an increase in mental distress. This is supported by lower household expenditures, increased rates of alcohol/drug abuse and lowered emotional wellbeing in affected populations. A subsample of previously displaced families shows higher risk of developing domestic violence. Policymakers should consider the multi-fold non-economic outcomes of natural disasters.
Keywords: H12; J12; O12; Q54; 330; Natural disasters; domestic violence; longitudinal family data